2016
DOI: 10.1186/s12862-015-0573-0
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of heat shock protein sequences, cis-regulatory elements, and expression profiles in the eusocial Hymenoptera

Abstract: BackgroundThe eusocial Hymenoptera have radiated across a wide range of thermal environments, exposing them to significant physiological stressors. We reconstructed the evolutionary history of three families of Heat Shock Proteins (Hsp90, Hsp70, Hsp40), the primary molecular chaperones protecting against thermal damage, across 12 Hymenopteran species and four other insect orders. We also predicted and tested for thermal inducibility of eight Hsps from the presence of cis-regulatory heat shock elements (HSEs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 81 publications
9
42
0
Order By: Relevance
“…For those that have, HSP70 synthesis has largely been the focus (Gehring and Wehner, 1995;Maisov et al, 2007). However, Nguyen et al (2016) recently showed that the primary inducible gene involved in HSR in Drosophila -hsp70 -has been completely lost in Hymenoptera, which instead employs two hsc70-4 paralogues. Like Gehring and Wehner (1995), we found that HSC70 is constitutively expressed in C. bombycina.…”
Section: Heat Stress and Gene Upregulationmentioning
confidence: 99%
See 4 more Smart Citations
“…For those that have, HSP70 synthesis has largely been the focus (Gehring and Wehner, 1995;Maisov et al, 2007). However, Nguyen et al (2016) recently showed that the primary inducible gene involved in HSR in Drosophila -hsp70 -has been completely lost in Hymenoptera, which instead employs two hsc70-4 paralogues. Like Gehring and Wehner (1995), we found that HSC70 is constitutively expressed in C. bombycina.…”
Section: Heat Stress and Gene Upregulationmentioning
confidence: 99%
“…The second study investigated hsp60, hsp75 and hsp90 expression in response to temperature in the wood ant Formica cinerea and found no significant effects (Ślipinśki et al, 2015). The third study compared heat-shock-related expression patterns of several hsp genes between Pogonomyrmex barbatus, an ant living in hot and arid climates, and Aphaenogaster picea, an ant living in cool woodlands (Nguyen et al, 2016). These authors showed that expression of hsc70-4, hsp83 and hsp40 was upregulated in response to heat stress and the species differed significantly in relative expression levels.…”
Section: Heat Stress and Gene Upregulationmentioning
confidence: 99%
See 3 more Smart Citations